Two new species of Cyrtodactylus (Squamata: Gekkonidae) from northern Laos, including new finding and expanded diagnosis of C. bansocensis - Schneider, Nicole; Luu, Vinh Quang; Sitthivong, Saly; Teynié, Alexandre; Le, Minh Duc; Nguyen, Truong Quang; Ziegler, Thomas (Zootaxa, 2020)
Two new Cyrtodactylus species are described from Houaphan and Luang Prabang provinces in Laos based on morphological and molecular data. Cyrtodactylus houaphanensis sp. nov. differs from all other Cyrtodactylus in the C. wayakonei species group by at least 3.3 % genetic divergence in the COI gene and can be diagnosed in morphology as follows: SVL 75.8 mm; supralabials 9 or 10; infralabials 8 or 9; ventral scales 35; dorsal tubercles in 20 rows at midbody; precloacal pores 6 in the male; femoral pores absent; subcaudals enlarged; five irregular, brown bands between limb insertions. The new species morphologically resembles C. chauquangensis and revealed to be a sister taxon to C. puhuensis according to our genetic analyses, from which it mainly differs in the absence of enlarged femoral scales. Cyrtodactylus ngoiensis sp. nov. differs from other closely related congeners by at least 11.6 % genetic divergence in the COI gene and can be diagnosed in morphology as follows: maximum SVL 95.3 mm; supralabials 6–9; infralabials 8–11; ventral scales 38–43; dorsal tubercles in 15–21 rows at midbody; enlarged femoral scales present; precloacal pores 7 in the male, 7 pitted scales in females; femoral pores 14 in the male, absent in females; five bright yellowish transverse dorsal bands; subcaudals enlarged. The new species is shown to be a member of the C. wayakonei species group, but morphologically resembles C. dumnuii from Thailand. According to our phylogenetic analyses, it is a basal taxon to a clade comprising C. spelaeus, C. chauquangensis, C. vilaphongi, C. cucphuongensis, C. puhuensis, C. houaphanensis, C. otai and C. bobrovi. Based on a new record of C. bansocensis from central Laos, which represents the first recorded female we provide a redescription of C. bansocensis including expanded diagnosis. In addition, an updated identification key for the Cyrtodactylus known from Laos is provided.